Non Government Organizations Contribution to Collaborative Governance Stages and Handling Collaborative Risk in Kulonprogo Regency - Murti, Awang Daru; Baiquni, Muhammad; Lele, Gabriel (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the contribution of Non-Government Organizations (NGOs) in the implementation of the tobacco control policy in Kulonprogo Regency based on the stages of collaboration, the risks of collaboration and the actions taken to overcome these risks. This study uses a qualitative method with a descriptive approach. Sources of data in this study used data from interviews, previous research and online mass media news data.Based on result study, NGO have contribution in every collaboration stages. This study measures collaboration based on the stages of collaboration including brainstorming, initial collaboration, maturation of thought, and implementation. NGO have contribution in every collaboration stages. The synergy between MTCC, The Union, and the Government of Kulonprogo also experienced several problems such as administrative problems, transparency, differences in vision and mission, recruitment of members that did not comply with the rules, and lack of coordination between institutions, especially the Regional Apparatus Organizations (OPD). The risks resulting from these problems include temporary suspension of collaboration activities, internal conflicts, incompetent members, difficulty in inter-agency coordination, and financial abuse. Overcoming this problem, the actors involved in the collaboration took several actions such as revising regulations and organizational structures, tightening the member recruitment process, improving communication and coordination, as well as collaborating in financial supply.